Effect of Thirst Challenge on ADH Levels in Patients with Bilateral Menière’s Disease - Steinbach, S.; Hundt, W.; Hamann, K. F.; Werner, J. A.; Mandic, R. (Experimental and Clinical Endocrinology & Diabetes, 2012)
The aim of the study was to investigate plasma ADH levels and plasma/urine osmolality in patients suffering from bilateral Menière’s disease since a disturbance in the water household after thirst challenge is a suspected pathogenic factor in the development of this disease. In this study the plasma ADH levels and plasma/urine osmolality of bilateral Menière’s disease patients under thirst challenge were investigated to show whether the water balance is affected. 9 patients with bilateral Menière’s disease and 9 healthy controls skipped water intake for 12 h. Plasma ADH, plasma/urine osmolality, and electrolytes were measured after this thirst period as well as 8 h later after food and fluid intake. During food and fluid intake the patients demonstrated a slightly higher plasma ADH level and plasma osmolality than controls, whereas at the end of the thirst period patients and the controls showed no significant change. Instead the urine osmolality differed significantly (p<0.001): showing a high urine osmolality in controls and an almost stable urine osmolality in patients after thirst challenge. This indicates that the water balance in patients is likely different from that of controls. These observations point to ADH and its target aquaporine 2 as keyplayers in the pathophysiological events leading to the development of Menière’s disease.
Keywords: bilateral Menière’s disease; thirst challenge; antidiuretic hormone; plasma osmolality; urine osmolality